A formal [4 + 1] cycloaddition reaction of Baylis–Hillman bromides with sulfur ylides: facile access to α-alkenyl lactones. Issue 13 (26th May 2022) - Hua, Ting-Bi; Ma, Yu-Hong; He, Xiao-Yu; Wang, Long; Yan, Jia-Ying; Yang, Qing-Qing
Abstract : A formal [4 + 1] cycloaddition reaction of Baylis–Hillman adducts with sulfur ylides has been developed for the first time. Abstract : A formal [4 + 1] cycloaddition reaction of Baylis–Hillman adducts with sulfur ylides has been developed for the first time. This protocol features high functional group tolerance and provides facile access to biologically interesting α-alkenyl lactones with generally high yields. Meanwhile, the DFT calculation of the pathways has also been performed.